Increased Chromosomal and Oxidative DNA Damage in Patients with Multinodular Goiter and Their Association with Cancer - Hamiyet Donmez-Altuntas; Fahri Bayram; Nazmiye Bitgen; Sibel Ata; Zuhal Hamurcu; Gulden Baskol (International Journal of Endocrinology)
Thyroid nodules are a common clinical problem worldwide. Although thyroid cancer accounts for a small percentage of thyroid nodules, the majority are benign. 8-Hydroxy-2′-deoxyguanosine (8-OHdG) levels are a marker of oxidative stress and play a key role in the initiation and development of a range of diseases and cancer types. This study evaluates cytokinesis-block micronucleus cytome (CBMN-cyt) assay parameters and plasma 8-OHdG levels and their association with thyroid nodule size and thyroid hormones in patients with multinodular goiter. The study included 32 patients with multinodular goiter and 18 age- and sex-matched healthy controls. CBMN-cyt assay parameters in peripheral blood lymphocytes of patients with multinodular goiter and controls were evaluated, and plasma 8-OHdG levels were measured. The micronucleus (MN) frequency (chromosomal DNA damage), apoptotic and necrotic cells (cytotoxicity), and plasma 8-OHdG levels (oxidative DNA damage) were significantly higher among patients with multinodular goiter. Our study is the first report of increased chromosomal and oxidative DNA damage in patients with multinodular goiter, which may predict an increased risk of thyroid cancer in these patients. MN frequency and plasma 8-OHdG levels may be markers of the carcinogenic potential of multinodular goiters and could be used for early detection of different cancer types, including thyroid cancer.